Perbedaan Massa Umbi Kentang Hitam (Soleneotemon Rotundifolius (Poir) J. K. Mort.) terhadap Kecepatan Pertumbuhan dalam upaya Pengembangan Petunjuk Praktikum Fisiologi Tumbuhan I - Rahayu, Rahmatul; Hajiriah, Titi Laily (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2015)
The research purpose is aimed to know the different mass of black potatoes (Soleneotemon rotndifolius (Poir) J.K Mort.) towards is growing speed. The type of the research in this study is true experimental research in which the research uses split plot design. The technique of data collecting method used in this study is direct observation. Meanwhile, the data analyzing technique used to analyze the data in this study is analysis of variance (ANOVA). The sampel in this research was given five different treatment is A in which the potato mass is 1 gr with water concentration 100%, the second treatment is is B wich the potato mass is 3 gr with water concentration 100%, the third treatment is C with the potato mass is 1 gr with water concentration 100%, fourth treatment is D with 6 gr potato mass is 1 gr with water concentration 100%, the last treatment is E with 7 gr potato mass is 1 gr with water concentration 100%. There were three repetition given to every single treatment. Based on the result of experiment, it was found that the number of the leafs is F-calculation 1.090, the huge of the leaft is 1.000 F-calculation, steam diameter is 0.837 t-calculation, the height of the steam is 0.0710 t-calculation, and the F-table is 0.837 the level of significance 0.05 and 5.99 at the level of significance 0.01. Thus, the study conluded that there is significant influence the different mass of black potatoes (Soleneotemon rotndifolius (Poir) J.K Mort.) towards its growing speed.